Evaluasi Program Aplikasi Partisipasi Masyarakat Dalam Perancangan Undang-Undang (SIMAS PUU) - Muhamad Arby Hariawan (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
As a program, Simas PUU application cannot be separated from evaluation that function to determine the achievement of program purposes. To find out the achievement of these purposes, this thesis use the program evaluation theory by Arnold Love. The research method used is descriptive quantitative which seeks to provide a comprehensive description of the research problem. Furthermore, to strengthen the argument, the research collected data using the method of distributing questionaires, interviews, and literature studies. The results of the research indicate that: (1) Simas PUU application has been able to realize the needs of the target group, (2) the formulated program plans and designs are following the program objectives., (3) the program implementation has served the target group carefully, and (4) the improvement of Simas PUU application has been running optimally. From the results of the research, the researcher formulated many recommendations, namely (1) The Center of The Drafting Laws as the program implementer must display entire Draft Laws and Academic Papers so public can convey their needs in the draft law in question, (2) make plans and program designs that are in accordance with the dynamics public, (3) provide rapid feedback on public aspirations, and (4) increase the number of strategic partners in the stakeholder database.